BASIC RULES AND METHODS OF COMPARATIVE HISTORICAL LINGUISTICS - Negmatova Motabar Dostmurodovna (Scholars Digest Publishing, 2023)
The position about the historical change of language is one of the general facts of linguistics today, although this fact became the property of the science relatively recently - at the end of the 18th - beginning of the 19th century. Comparative-historical linguistics is a branch of linguistics whose object is o 'interrelated, ie. genetically related languages. In comparative historical linguistics, we talk about establishing relationships between related languages and describing their evolution in time and space; comparative-historical linguistics uses the comparative-historical method as the main research tool; the most general form of research is comparative-historical grammar and etymological dictionaries (lexicon).
Keywords: comparative-historical method, linguistics, synchronicity, aspects, linguist.